Housing, Inequality and Sociology: A Comment on Pragmatic Socioeconomics. Issue 2 (15th March 2022) - Atkinson, Rowland; Jacobs, Keith
ABSTRACT: In this brief article, we reflect on the contribution of Martin Lux and Petr Sunega to the role of sociology in the domain of housing economics. Applauding the attempt at injecting a more sociologically informed housing economics, we draw attention to the continuous need to guard against over-abstraction and to ensure that housing's role as a major source of material inequality in many societies must be fully recognized.